2020
DOI: 10.1002/htj.21663
|View full text |Cite
|
Sign up to set email alerts
|

Binary chemical reaction with activation energy in radiative rotating disk flow of Bingham plastic fluid

Abstract: This article presents flow, heat and mass transfer phenomena in Bingham plastic fluid. The flow channel is considered to be a rotating disk with a slip which is different in span and streamwise directions, and heat transfer is investigated using dissipation term of the fluid. Arrhenius activation energy and binary chemical reaction are the imperative features of the study of mass transfer. Bingham plastic fluid and anisotropic slip arethe key factors of the study due to their numerous applications in manufactu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In light of this, Mortimer and Eyring 26 developed a theory for the Soret and Dufour effect using the elementary transition state method. Many scholars followed this study, including Tsai and Huang 27 and Hayat et al 28 Non-Newtonian fluids are more suited to the chemical engineering sector than Newtonian fluids such as Casson fluid, Sutterby fluid, Bingham plastic fluid (Khan et al 29 ), and so forth. The Carreau fluid is one such Non-Newtonian fluid (NF) that has lately acquired a lot of traction because of its advantage over the power-law viscosity model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of this, Mortimer and Eyring 26 developed a theory for the Soret and Dufour effect using the elementary transition state method. Many scholars followed this study, including Tsai and Huang 27 and Hayat et al 28 Non-Newtonian fluids are more suited to the chemical engineering sector than Newtonian fluids such as Casson fluid, Sutterby fluid, Bingham plastic fluid (Khan et al 29 ), and so forth. The Carreau fluid is one such Non-Newtonian fluid (NF) that has lately acquired a lot of traction because of its advantage over the power-law viscosity model.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐Newtonian fluids are more suited to the chemical engineering sector than Newtonian fluids such as Casson fluid, Sutterby fluid, Bingham plastic fluid (Khan et al 29 ), and so forth. The Carreau fluid is one such Non‐Newtonian fluid ( NF ) that has lately acquired a lot of traction because of its advantage over the power‐law viscosity model.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the developed DBD Kr/Cl 2 excilamp has an instant start-up with full radiation output ( ∼ 2.0 mW/cm 2 ), in contrast to the mercury-based UV-C lamp, which has a start-up time of about 2.5 min 55 . The thermal conductivity of the treated suspension due to various reactive species can also be estimated by using numerical modelling techniques 56,57 . The Kr/Cl 2 excilamp is positioned above the water level, which has produced two important benefits.…”
Section: Toxicity Analysis and Reusability Of Treated Wastewater For ...mentioning
confidence: 99%
“…Earlier on, Shafique [3] studied the impact of activation energy and chemical reaction on Maxwell fluid flow in a rotating frame. More details on binary chemical reaction can be found in ( [5][6][7][8][9], [44,45]). Casson fluid is one of the members of non-Newtonian fluids that exhibits yield stress and high shear viscosity [10].…”
Section: Introductionmentioning
confidence: 99%